(untitled) (Research, Society and Development, 2018)
Air pollution is a recurring problem in urban and industrial centers and causes impacts on the environment and mainly on public health. In an attempt to monitor these impacts, the use of air bioindicators was very effective, especially since bioindicators have a great sensitivity to air pollutants. The objective of this paper was to evaluate the air quality in three distinct points in Itabira town/MG, using lichens as bioindicators. The methodology used in this research was passive biomonitoring, where the study of the lichen community was associated to the Air Purity Index – (IPA). The three sampled points were defined according to the proximity of the iron ore mines and near the local vehicles flow. The results of the IPA showed that Itabira has an acceptable air quality and the lowest IPA value was obtained for the location closest to the mine.